The National Institute of Health and the Italian Poison Centers Network: results of a collaborative study for the surveillance of exposures to chemicals - Giordano, F.; Pennisi, L.; Fidente, R. M.; Spagnolo, D.; Mancinelli, R.; Lepore, A.; Draisci, R. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The Public Health Surveillance Systems are essential to improve and protect public health, as highlighted by the World Health Organization. According with this consideration, a systematic collaboration between the National Institute of Health and the Poison Centers of Northern, Central and Southern Italy was established. Its aim was to improve the national network for the surveillance of dangerous exposures to chemicals. The developed network provided harmonized data essential for evidence-based interventions and significantly ameliorated the data flow between the Poison Centers and the Central Health Institutions. Methods. The improvement of the system was obtained through several actions, such as the development of the “Online Surveillance Card” for the detection of sentinel events in real time and the harmonization of the data collection flow, including the product categorization according to the European Product Categorization System. Data analysis was carried out by Microsoft’s IBM SPSS Statistics version 26, Access and Excel. Results. Important information was obtained, regarding also exposures to chemicals and their management in pediatric populations. The surveillance network was proved effective not only under “normal” conditions but also to promptly monitor changes during exceptional health emergencies, such as the COVID-19 pandemic. During the 2020 lockdown the surveillance system registered a significant increase in the frequency of exposures to disinfectants (p-value=0.002), an evidence that highlighted the need of tailored intervention. Conclusions. This Italian Project model proves to be reliable and suitable to be transferred to other European countries, in order to realize an European Poison Centers’ Network, able to overcome unsolved health problems and to globally improve the “evidence-based” prevention of exposures to chemicals.